Endoscopic Therapy in Crohn's Disease: Principle, Preparation, and Technique. Issue 9 (September 2015) - Chen, Min; Shen, Bo
Abstract : Abstract: Stricture and fistula are common complications of Crohn's disease. Endoscopic balloon dilation and needle-knife stricturotomy has become a valid treatment option for Crohn's disease–associated strictures. Endoscopic therapy is also increasingly used in Crohn's disease–associated fistula. Preprocedural preparations, including routine laboratory testing, imaging examination, anticoagulant management, bowel cleansing and proper sedation, are essential to ensure a successful and safe endoscopic therapy. Adverse events, such as perforation and excessive bleeding, may occur during endoscopic intervention. The endoscopist should be well trained, always be cautious, anticipate for possible procedure-associated complications, be prepared for damage control during endoscopy, and have surgical backup ready. In this review, we discuss the principle, preparation, techniques of endoscopic therapy, as well as the prevention and management of endoscopic procedure-associated complications. We propose that inflammatory bowel disease endoscopy may be a part of training for "super" gastroenterology fellows, i.e., those seeking a career in advanced endoscopy or in inflammatory bowel disease. Abstract : Article first published online 19 May 2015.